HUBUNGAN ANTARA PENGETAHUAN, PERILAKU ERGONOMI FISIK SISWA SMA SAAT BELAJAR DAN KEJADIAN NYERI PUNGGUNG PADA SISWA SMA JAKARTA BARAT - Yovita Dwi Setiyowati; Yohana Rani Hartati (School of Nursing, Faculty of Medicine, Lambung Mangkurat University., 2022)
Low back pain is a musculoskeletal disorder caused by poor sitting posture. The incident of low back pain among students are effected by knowledge, computer use, and sitting posture.The purpose of this study was known the relationship among knowledge, physical ergonomic behaviour, and low back pain incidence at Senior High School Jakarta. This research used a quantitative methode with descriptive correlative research design and cross-sectional approach. The total sample was 114 students with purposive sampling technique. The result use Chi-Square test showed that knowledge was significant association (p <0,05) with ergonomic behaviour, and ergonomic behaviour was significant asociation with low back pain incidence (p-value = 0.000).